Ecosystem multifunctionality lowers as grasslands under restoration approach their target habitat type. Issue 1 (16th June 2022) - DeCock, Eva; Moeneclaey, Iris; Schelfhout, Stephanie; Vanhellemont, Margot; De Schrijver, An; Baeten, Lander
Abstract : Biodiversity is declining at a rapid pace and, with it, the ecosystem functions that support ecosystem services. To counter this, ecosystem restoration is necessary. While the relationship between biodiversity and ecosystem functioning has been studied in depth, the relationship between ecosystem restoration and ecosystem functioning is studied less. We performed an observational study in grasslands undergoing restoration management toward Nardus grassland. Eight ecosystem functions, representing flows of energy, matter or information between functional compartments, were measured across five successive restoration phases along the restoration gradient. The levels of functioning were then compared along the gradient for both the individual functions and a multifunctionality index. We hypothesized that plant richness increases when grasslands are more restored and this increase in biodiversity is paralleled by an increase in ecosystem functioning. In our study, the degraded grasslands, generally occurring on more nutrient‐rich soils, were dominated by competitive fast‐growing species, resulting in higher process rates and thus in higher, faster functioning. Likewise, more restored grasslands exhibited slower process rates and, thus, lower functioning. When studying ecosystem functioning, value judgments are easily made. Especially in a restoration context, high functioning does not necessarily equals well functioning, as this depends on the stakeholder perspective. We need to ask ourselves if a high functioning ecosystem is most desirable, especially in a restoration or conservation context. Policy frameworks will need to balance these goals.